Cryptosporidium parvum infection alters the intestinal mucosa transcriptome in neonatal calves: impacts on epithelial barriers and transcellular transport systems - Veshkini, Arash; Kühn, Christa; Dengler, Franziska; Bachmann, Lisa; Liermann, Wendy; Helm, Christiane; Ulrich, Reiner; Delling, Cora; Hammon, Harald M. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionCryptosporidium parvum (C. parvum) is the most prevalent enteric protozoan parasite causing infectious diarrhea in neonatal calves worldwide with a direct negative impact on their health and welfare. This study utilized next-generation sequencing (NGS) to deepen our understanding of intestinal epithelial barriers and transport mechanisms in the pathophysiology of infectious diarrhea in neonatal calves, which could potentially unveil novel solutions for treatment.MethodsAt day 1 of life, male Holstein-Friesian calves were either orally infected (n = 5) or not (control group, n = 5) with C. parvum oocysts (in-house strain LE-01-Cp-15). On day 8 after infection, calves were slaughtered and jejunum mucosa samples were taken. The RNA was extracted from collected samples and subjected to sequencing. Differentially expressed genes (DEG) between the infected and CTRL groups were assessed using DESeq2 at a false discovery rate < 0.05 and used for gene ontology (GO) and pathway enrichment analysis in Cytoscape (v3.9.1).Results and discussionTo study the pathophysiology of infectious diarrhea on intestinal permeability, 459 genes related to epithelial cell barrier integrity and paracellular and transmembrane transport systems were selected from 12,908 identified genes in mucus. Among, there were 61 increased and 109 decreased gene transcripts belonged to adhesion molecules (e.g. ADGRD1 and VCAM1), ATP-binding cassette (ABC, e.g. ABCC2 and ABCD1) and solute carrier (SLC, e.g. SLC28A2 and SLC38A3) transporters, and ion channels (e.g. KCNJ15). Our results suggest deregulation of cellular junctions and thus a possibly increased intestinal permeability, whereas deregulation of ABC and SLC transporters and ion channels may influence the absorption/secretion of amino acids, carbohydrates, fats, and organic compounds, as well as acid-based balance and osmotic hemostasis. Besides pathogen-induced gene expression alterations, part of the DEG may have been triggered or consequently affected by inflammatory mechanisms. The study provided a deeper understanding of the pathophysiology of infectious diarrhea in neonatal calves and the host-pathogen interactions at the transcript level. For further studies with a particular focus on the transport system, these results could lead to a new approach to elucidating pathophysiological regulatory mechanisms.